The Possibility of Applying the Dimensions of Entrepreneurial Marketing in Asia cell Company in Kurdistan/ Iraq: A Descriptive Analytical Study of the Opinions of Sample of Administrative Leaders in the Company of Asia Cell Telecom in Kurdistan Iraq - Mohammed Al-Azawi, Mohammed Abdul Wahab; Jamal, Zhila (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
In light of the continuous changes in the marketing business environment, it was imposed on organizations to change their traditional view of markets to embrace entrepreneurial marketing of their products. It is considered a pioneer of modern marketing trends to keep pace with changes and adapt to their result. Based on that, the research aims to analyze the opinions of employees of Asiacell communications company to demonstrate access to entrepreneurial marketing services in light of the competition it faces where the following questions identified the research problem: what is the extent of awareness and knowledge of officials in the company under discussion about the concept and importance of entrepreneurial marketing, and what are the dimensions that can be adapted to apply the concept of entrepreneurial marketing in the company (45) questionnaires were distributed to a sample of workers in the company in question and were excluded five forms not valid for analysis and approval of (40) forms only by 86%. The researcher reached a set of conclusions, the most important of which are: officials desire to apply entrepreneurial marketing dimensions. The company's management is keen to encourage workers financially and morally for its services in a pilot. In light of the conclusions, several recommendations were presented, the most important of which are: The company's management must adhere to the dimensions of entrepreneurial marketing to meet the market challenges of competition. In addition, the company has trained and developed workers in modern marketing methods by introducing courses in this field.